Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan terhadap Kinerja Karyawan melalui Disiplin Kerja (Studi pada Karyawan Patra Jasa Convention Hotel Semarang) - Az Zahra, Salma Fatimah; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of the this research is to find Â the effect of work environment and leadership towards employee performance through the work discipline. Good level of employee performance and the low level of absenteeism indicates good discipline at Patra Jasa Convention Hotel Semarang. The respondents of this research are Â employees of Patra Jasa Convention Hotel Semarang. Data collected through distribution of questionnaires towards 107 permanent employees with purposive sampling. However, only 105 data Â can be processed. The techniques of data testing in this research includes validity test by factor analysis, reliability test, classical assumption test, multiple linear regression, path analysis, and the Sobel test to examine the mediation effect with SPSS 16.0.The results of this research indicates that work environment and leadership have positive influence on the discipline of work and employee performance. The analysis also shows that there is a mediation effect of work discipline on employee performance